2011
DOI: 10.1007/s00284-011-9998-x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Characterization and Diversity of Insecticidal Crystal Protein Genes of Bacillus thuringiensis Native Isolates from Soils of Andaman and Nicobar Islands

Abstract: Bt strains were isolated from soils of Andaman and Nicobar Islands and characterized by microscopic and molecular methods. Diversity was observed both in protein and cry gene profiles, where majority of the isolates showed presence of 65 kDa protein band on SDS-PAGE while rest of them showed 130, 72, 44, and 29 kDa bands. PCR analysis revealed predominance of cry1I and cry7, 8 genes in these isolates. The PCR screening strategy presented here led us to identify putative novel cry genes which could be active ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…For larvae exposed to Cry3Aa protoxin treated media the mortality increased from 22 ± 2.00% (1000 ng cm −2 ) to 30.2 ± 0.63% (10,000 ng cm −2 ). Higher doses (20,000 and 30,000 ng cm −2 ) had little additional effect on mortality and produced higher variability . It is coherent with a physiological meaning (pH, proteases or changes in toxin–receptor interaction on the apical brush border of the midgut microvillae).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…For larvae exposed to Cry3Aa protoxin treated media the mortality increased from 22 ± 2.00% (1000 ng cm −2 ) to 30.2 ± 0.63% (10,000 ng cm −2 ). Higher doses (20,000 and 30,000 ng cm −2 ) had little additional effect on mortality and produced higher variability . It is coherent with a physiological meaning (pH, proteases or changes in toxin–receptor interaction on the apical brush border of the midgut microvillae).…”
Section: Discussionsupporting
confidence: 61%
“…The cry3A gene was amplified, cloned, and sequenced. Total DNA isolated from native Bt strains from Andaman and Nicobar Islands , Jammu and Kashmir (Unpublished data) was amplified (Fig. ) using gene specific primers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experience has shown that the resistance conferred by a single Bt gene has the potential to break down as the target insect pest mutates and adapts to defeat the Bt trait [10]. To cope with the emergence of resistant insect population, there is great interest in finding novel insect-resistant gene with higher toxicity and/or wider spectrum [11]. In this study, we tried to develop new transgenic poplar with new insect genes other than Cry1Ac , in order to cope with the potential resistant insect in the future.…”
Section: Introductionmentioning
confidence: 99%